Q.23 x 2 – 6 + 55y + 6y y = 3 ​


Q.

23 x 2 – 6 + 5

5y + 6y

y = 3 ​


PEMBAHASAN

Diketahui

  • 23 x 2 – 6 + 5
  • 5y + 6y
  • y = 3

Ditanya

  • Hasil ?

Perampungan

23 x 2 – 6 + 5

( 23 x 2 ) – ( 6 + 5 )

( 23 + 23 ) – 11

46 – 11


3


5

5y + 6y

5(3) + 6(3)

( 5 x 3 ) + ( 6 x 3 )

15 + 18


3


3

Kesimpulan

Maka, dapat disimpulkan bahwa hasil dari 23 x 2 – 6 + 5 adalah
{{ \boxed{\sf \: 35}}}
dan hasil berpangkal (5y + 6y)

(y = 3 ) ialah
{{ \boxed{{{\sf \:33}}}}}

\sf - Cdy


ramadhanifadhillah23


Jawaban :

Soal no 1

23 x 2 – 6 + 5 =
= ( 23 x 2 )
= ( 46 )
= ( 5 + 6 )

= 11

= 46 – 11

= 35

23 x 2 – 6 + 5 =


35

Soal no 2




Diketahui :

y = 3

Ditanya :

5y + 6y = ?

Jawaban dan cara pengerjaan :




5( y ) + 6( y ) =
5( y ) = 5 x 3
5( y ) = 15

6( y ) = 6 x 3
6( y ) = 18

5y + 6y = ( 15 + 18 )
=


33

SEMOGA MEMBANTU .




banner

×